IMPLEMENTING ROTATION MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES IN SCIENCE SUBJECT AT ELEMENTARY SCHOOL - Roudlotul Halimi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to determine the effect of rotation model on students’ learning outcomes at grade VI in science subject. This research used experimental research methods. The subjects in this study were 34 students at grade VI SDN Krajanbogo Bonang Demak as the experimental class and 22 students at class VIA SDN Sidomulyo 2 Wonosalam Demak as the control class. The result of N-Gain score test showed that the experimental class (applying rotation model) had an average N-Gain score of 66.44% which fell into the “Quite effective” category. Meanwhile, the application of the conventional model to the control class obtained an average N-Gain score of 39.30% in the category of “Ineffective”. Meanwhile, the effectiveness test using the paired sample t test found that the significance value (2-tailed) was 0.000 < 0.05. In addition to the significance value, the value of t count > t table which was 38.152 > 2.035. From these results, it was concluded that the application of the rotation model gave a significant impact on students’ learning outcomes in science subject for grade VI elementary schools.